2. Oblicz wartość wyrażenia:

a) (x + 1)(x - 1) + (x + 2)(x - 2) - (x+3)(x - 3)
dla x = √3

b) (1 - 2.0) (1 + 2x) + (1 - 3x)(1+ 3x) - (1 - 4x)(4x + 1) dla x = √5

c) (2x - 1)^2 - (2x - 1)(1+ 2x) - (2x + 1)^2
dla x = √2​



Odpowiedź :

Odpowiedź:

a) (v3)² - v3 + v3 - 1 + (v3)² -2(v3) + 2(v3) - 4 - (v3)² + 3(v3) - 3(v3) + 9 = 2(v3)² + 4 = 2 × 3 + 4 = 10

b) 1 + 2v5 - 2v5 - (2v5)² + 1 + 3v5 - 3v5 - (3v5)² - 4v5 - 1 + (4v5)² + 4v5 = 1 - (2v5)² + 1 - (3v5)² - 1 + (4v5)² = -20 - 45 + 80 + 1 = -65 + 81 = 16

c) (2v2 - 1)² - (2v2 - 1)(1+2v2) - (2v2 +1)² = 7 - 2v2 - (2v2)² + 1 + 2v2 - 7 = -8 + 1= -7

Szczegółowe wyjaśnienie:

np. v2 = pierwiastek z 2